Transgenerational Effects of Trauma in Midlife: Evidence for Resilience and Vulnerability in Offspring of Holocaust Survivors - Shrira, Amit (2011)
Despite abundant research on offspring of Holocaust survivors (OHS), it is relatively unknown how they function in middle-age. Transgenerational effects of the Holocaust may be stronger among middle-aged OHS as they previously suffered from early inclement natal and postnatal environment and now face age-related decline. Yet, middle-aged OHS may successfully maintain the resilience they demonstrated at younger age. This study performed a wide-spectrum functional assessment of middle-aged OHS and comparisons (N = 364) drawn from the Israeli component of the Survey of Health, Ageing, and Retirement in Europe (SHARE-Israel). OHS, and especially those with two survivor parents, reported a higher sense of well-being, but more physical health problems than comparisons. The discussion provides possible explanations for this mixed functional profile.